2014
DOI: 10.1186/1476-4598-13-98
|View full text |Cite|
|
Sign up to set email alerts
|

The Bcl-2/xL inhibitor ABT-263 increases the stability of Mcl-1 mRNA and protein in hepatocellular carcinoma cells

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the major causes of mortality. ABT-263 is a newly synthesized, orally available Bcl-2/xL inhibitor that shows promising efficacy in HCC therapy. ABT-263 inhibits the anti-apoptotic activity of Bcl-2 and Bcl-xL, but not Mcl-1. Previous reports have shown that ABT-263 upregulates Mcl-1 in various cancer cells, which contributes to ABT-263 resistance in cancer therapy. However, the associated mechanisms are not well known.MethodsWestern blot, RNAi and CCK-8 assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 42 publications
6
50
0
Order By: Relevance
“…ABT263 is an orally bioavailable small molecule inhibitor of Bcl-2 family proteins that binds with high affinity to Bcl-2 and Bcl-xL, and antagonizes their anti-apoptotic function (20). In the present study, ABT263 (≤2 µM) treatment resulted in upregulated Mcl-1 expression, in agreement with a previous report (21). However, ABT263 (≤2 µM) did not induce apoptotic cell death in BT474 breast cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…ABT263 is an orally bioavailable small molecule inhibitor of Bcl-2 family proteins that binds with high affinity to Bcl-2 and Bcl-xL, and antagonizes their anti-apoptotic function (20). In the present study, ABT263 (≤2 µM) treatment resulted in upregulated Mcl-1 expression, in agreement with a previous report (21). However, ABT263 (≤2 µM) did not induce apoptotic cell death in BT474 breast cancer cells (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…ERK activation inhibits the processing of caspase-8 and Bid, thereby turning off the mitochondrial amplification loop [26,27]. Previous studies showed that Mcl-1 protein expression is enhanced due to ERK activation [28][29][30]. In our study, we observed that activation of ERK and protein level of MCL-1 decreased in Msi1 knockdown LH86-TR cells whereas increased in Msi1 overexpressing LH86 cells.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, the human hepatocellular carcinoma cancer often overexpresses Mcl-1, probably because of the various apoptosis inducing factors such as hypoxia, pH imbalances, and altered metabolism in which tumors reside, but also because of the benefits of Mcl-1 protein for cytoprotection [20,21].…”
Section: Discussionmentioning
confidence: 99%